Means of Proof in the Crime of Adultery and its Legal Validity (A Jurisprudential Study Compared to Positive Law) - Al Sheehah, Ahmad Abdulrahman (Journal of Posthumanism, 2024)
Islamic jurisprudence relies on certain methods to prove the crime of adultery that leave no room for doubt about the commission of this crime, such as confession and admission of the crime, and the testimony of four just witnesses. Some modern methods have emerged in our present age, such as photography, video recording, and DNA fingerprinting, through chat programs and the like. This necessitates a reconsideration of the means of proving this crime and the possibility of relying on contemporary methods to prove it. The research reached a number of conclusions, the most important of which is that Islamic law sets precise conditions that are difficult to meet or exist to prove adultery. Jurists agreed that adultery is proven by one of two things: confession and admission, and evidence. They differed on its proof by circumstantial evidence. None of these modern methods are considered a means of proving the crime of adultery, because each of them is subject to possibility. Rather, these methods are taken as acceptable evidence, but they cannot be relied upon unless they contain elements of protection against forgery, imitation, and tampering.